Current Status and Development Trend of Look-Ahead While Drilling Technology - Yan Sen; Gao Wenkai; Zhang Xiaohui; Wang Jiajin; Zhang Chunhua; Jia Hengtian (Shiyou jixie, 2025)
As one of the key emerging technologies in the field of logging while drilling （LWD）， the look-ahead wile drilling （LAWD） technology can perform real-time detection on undrilled formation in front of the bit， effectively reducing the risk of drilling accidents and improving drilling efficiency. In this paper， the LAWD technology was classified， the working principles of electromagnetic LAWD， acoustic LAWD and seismic LAWD were introduced， and their respective advantages and disadvantages were compared. The development history of LAWD tools and instruments was briefly described， and their application was analyzed. Moreover， it is indicated that the fusion of multiple methods is a key trend of LAWD technology in the future. Finally， the following suggestions are put forward： （1） the electromagnetic LAWD technology should develop towards multi-frequency and multi-spacing measurement mode； （2） the research on the phased array acoustic LAWD theory and technology should be strengthened， or the technology such as enhancing the look-ahead acoustic wave energy by pre-positioning the ultrasonic transducer should be explored to lay a technical foundation for the development of subsequent acoustic LAWD instruments； and （3） the research and development of VSP while drilling technology， including the development of high-accuracy sensors and the exploration of using downhole vibroseis to replace drill-bit source should be increased， so as to overcome the problem of PDC bit source. The research results provide technical support for the efficient and safe development of oil and gas resources in China.